Development of quizizz application assessment based on the TaRL approach in learning to identify the main ideas - Winahyu, Ineke Sukma Winahyu; Purwati, Panca Dewi (Indonesian Research Journal in Education |IRJE|, 2025)
This research aims to explain how the Quizizz application, used with the Teaching at the Right Level (TaRL) approach, was designed and tested to help fourth-grade students improve their reading comprehension, specifically in finding the main idea of informative texts. The method used is research and development (R&D) with the Borg & Gall model, with trials on nine students (small group) and 26 students (large group). This assessment integrates local wisdom content in informative text with gamification through the Quizizz application. The validation results show that the assessment is highly feasible, scoring 88.5 (media) and 89.7 (material). The effectiveness of the assessment is evidenced by an increase in the average pre-test score from 37.69 to 86.19 in the post-test and student completeness from 0% to 100%. Statistical tests showed significant differences before and after using the assessment, with an N-Gain score of 0.827908 (high category), proving their effectiveness in improving students' reading comprehension. This assessment is an evaluation tool that encourages active student involvement.